The Effect of the addition of pre-fermented juice and soluble carbohydrates to alfalfa silage on silage quality - Aydin, SS (Journal of the Hellenic Veterinary Medical Society, 2024)
In this study, it was aimed to determine the effects of fermented natural lactic acid bacteria (LAB) and different soluble carbohydrate sources on silage quality characteristics, in vitro organic matter digestion (IVOMD), metabolic energy (ME) and in vitro methane gas formation in alfalfa (Medicago sativa L.) silage. In the study, an analysis (pH, total LAB, yeast, mold, LA, AA, and LA/AA) was conducted on the naturally fermented lactic acid bacteria liquid prepared from alfalfa plants with a 3% molasses addition. While the silage prepared from the pure alfalfa plant in the study constituted the control group (i), the experimental groups; (ii) PFJ + pure alfalfa silage, (iii) PFJ + 1.5% molasses added alfalfa silage, (iv) PFJ + 1.5% fructose added alfalfa silage, (v) PFJ + 1.5% sucrose added alfalfa silage. In the study, the differences between the groups were statistically significant for the dry matter (DM), acid detergent insoluble fiber (ADF), IVOMD, metabolic energy (ME) and methane (CH4) values. When the fermentation characteristics (pH, NH3-N, LA, AA, LA/AA, LA/AA, and yeast-mold after aerobic stability) of the prepared silages were examined, the differences between the groups were found to be statistically significant. When analyzed in terms of all parameters, it was determined that the addition of PFJ + 1.5% sucrose added alfalfa silage had positive effects on silage quality, the fermentation characteristics and in vitro organic matter digestion